IEEE/ACM Joint Conference on Digital Libraries 2014
DOI: 10.1109/jcdl.2014.6970216
|View full text |Cite
|
Sign up to set email alerts
|

On Cloud deployment of digital preservation environments

Abstract: Although migrating library applications to Cloud environment is not an easy task, many libraries are interested in using Cloud infrastructure services broadly across their businesses, whether is about a Public, Private or Hybrid Cloud. One of the migration expectations is the scalability of digital preservation architectures in Cloud environments. In this paper we address the scalability and portability of storage and compute platforms, which combine storage of large datasets and their processing. Concretely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The same is true for OpenStack, where nodes, which, for example, are responsible for computing, storage, and networking, have to be configured. Configuring large quantities of nodes is a common task for configuration management tools [11][14] [15]. Therefore, Puppet modules that configure and provision these tools were selected.…”
Section: A Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The same is true for OpenStack, where nodes, which, for example, are responsible for computing, storage, and networking, have to be configured. Configuring large quantities of nodes is a common task for configuration management tools [11][14] [15]. Therefore, Puppet modules that configure and provision these tools were selected.…”
Section: A Methodologymentioning
confidence: 99%
“…Several authors [11][14] [15] describe grid computing scenarios in which configuration management tools are used. The contribution of this work is argued to be the concept for automating the management of grid computing landscapes.…”
Section: Previous Research On Configuration Management Toolsmentioning
confidence: 99%
“…With the cost and institutional burden of data center operations transferred to the cloud, NARA is able to concentrate its assets more fully and efficiently on the core mission of developing and utilizing the tools and procedures needed to process and preserve the permanently valuable records of the United States. Research has shown that the underlying cloud infrastructure becomes a tool itself in fulfilling this mission of preservation and public access, rather than an impediment to its accomplishment (Han, 2015;Nguyen & Lake, 2011;Pop, Neagul, & Petcu, 2014). Cloud technology is inherently based on an information architecture that provides significant redundancy, and thus provides for one of the hallmarks of electronic preservation: that there will be several copies of each electronic record held safely in geographically dispersed areas.…”
Section: Why the Cloud?mentioning
confidence: 99%
“…Stated simply, it is often impossible for the agency to know how much content will need to be processed and when it will arrive. Thus, the wellestablished capability in a cloud environment to add storage and computing power for preservation functions virtually upon demand (Nguyen & Lake, 2011;Pop, Neagul, & Petcu, 2014) becomes more than just a convenience -it can be considered an essential component of the agency's ability to respond to its mission. This flexibility is particularly valuable when considering the budgetary environment in which NARA and all government agencies operate -highly constrained and often unpredictable and inflexible.…”
Section: Why the Cloud?mentioning
confidence: 99%